2022
DOI: 10.1155/2022/7420641
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation-Based Model for Analyzing the Correlation between GDP Index and Quality of Life

Abstract: As the information carrier of the social economy, the quality of statistical data has become more concerned and sensitive in the society and the data quality of GDP, as one of the core aggregate indicators of national economic accounting, has received more extensive attention. Government statistical departments have placed data quality in a strategic position in the development of statistical undertakings, and the assessment of GDP data quality is an important part of their data production management process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…With the help of these studies, a much deeper understanding of the financial situation of households can be obtained than, for example, with data from the World Bank, which focuses on objective financial dimensions. Jing (2022), in an ordered logit model, re-analysed the determinants of subjective economic well-being and showed that higher values of the material wealth index and income quartiles improve economic well-being while being unemployed, working part-time or on benefits lowers it. In addition, the results obtained by Jing (2022) indicate that people with higher education are more satisfied with their economic situation, even after taking into account income and wealth effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of these studies, a much deeper understanding of the financial situation of households can be obtained than, for example, with data from the World Bank, which focuses on objective financial dimensions. Jing (2022), in an ordered logit model, re-analysed the determinants of subjective economic well-being and showed that higher values of the material wealth index and income quartiles improve economic well-being while being unemployed, working part-time or on benefits lowers it. In addition, the results obtained by Jing (2022) indicate that people with higher education are more satisfied with their economic situation, even after taking into account income and wealth effects.…”
Section: Discussionmentioning
confidence: 99%
“…Jing (2022), in an ordered logit model, re-analysed the determinants of subjective economic well-being and showed that higher values of the material wealth index and income quartiles improve economic well-being while being unemployed, working part-time or on benefits lowers it. In addition, the results obtained by Jing (2022) indicate that people with higher education are more satisfied with their economic situation, even after taking into account income and wealth effects. Researchers also point to the lack of a clear relationship between economic development (described by GDP) and subjective assessments of the financial situation of households.…”
Section: Discussionmentioning
confidence: 99%